Trends in the incidence of peripheral vestibular disorders: a Nationwide population-based study - Hung, Shih-Han; Xirasagar, Sudha; Dang, Luong Huu; Chen, Yen-Chun; Cheng, Yen-Fu; Lin, Herng-Ching; Chen, Chin-Shyan (Frontiers in Neurology, 2023)
Purpose This study aimed to examines the long-term trend of incidence of peripheral vestibular disorders between 2010 and 2018 in Taiwan. Methods Study-eligible patients were identified from Taiwan’s Longitudinal Health Insurance Database 2005 maintained by the Ministry of Health and Welfare in Taiwan. We retrieved 230,566 patients with a first-time diagnosis of peripheral vestibular disorders between 2010 and 2018. We calculated annual incidence rates of peripheral vestibular disorders per 100,000 population. We used the annual percent change (APC) to test the trend of peripheral vestibular disorders over time. Results The mean annual incidence rate of peripheral vestibular disorders during the study period was 1489.6 per 100,000 population. Incidence showed a statistically significant steady decrease from 2010 to 2018 with a mean APC of −6.15% (95% CI = −6.97% −5.32%). The decline was led by Meniere’s disease (APC = −9.83, 95% CI = −10.66% −8.99%), followed by benign paroxysmal positional vertigo (APC = −3.69, 95% CI = −4.53% −3.03%), vestibular neuritis (APC = −7.85, 95% CI = -8.96 −6.73), and other peripheral vestibular dizziness (APC = −5.56, 95% CI = −6.69% −4.43%). Conclusion The incidence of peripheral vestibular disorders, overall, and the four major subgroups, benign paroxysmal positional vertigo, Meniere’s disease, vestibular neuritis, and other peripheral vestibular dizziness, all decreased substantially, year by year within the 2010–2018 period.